Isolation of phenolic constituents from Rhododendron yunnanense flowers as a potent cyclooxygenase-2 and vascular endothelial growth factor receptor-2 inhibitor: Phytochemical and molecular simulation studies - Mohamed Salaheldin Ahmed Abdelkader, Reda Ahmed Abdelhamid, Mohamed Ezzat Abouelela, Mostafa Ezzat Rateb, Marwa Hassan Ahmed (Journal of Applied Pharmaceutical Science, 2021)
The genus Rhododendron is a rich source of phenolic compounds that possess a wide range of biological activities. Phytochemical investigation of the methanolic extract of the flowers of Rhododendron yunnanense Franch. led to the isolation and characterization of 13 phenolic compounds isolated for the first time from this plant species. These compounds were identified as quercetin (1), quercitrin (2), avicularin (3), taxifolin-3-O-α-L-arabinoside (4), azalein (5), kaempferol-3-O-rhamnoside (6), kaempferol-4?-methoxy-3-O-rhamnoside (7), kaempferol-3-β-D-glucopyranoside (8), catechin (9), epicatechin (10), catechin-3-O-gallate (11), 5-O-Z-p-coumaroylquinic acid methyl ester (12), and 5-O-caffoeylquinic acid methyl ester (13). The structures of compounds 1–13 were determined by 1D and 2D nuclear magnetic resonance and comparison with reported spectral data. A molecular simulation study was carried out on the binding mode of the isolated compounds as anti-inflammatory agents through cyclooxygenase 2 (COX-2) inhibition and as mediators of tumor angiogenesis through vascular endothelial growth factor inhibition. The docking results of the isolated compounds revealed promising binding affinities to the examined enzymes. Compound 2 showed predominant affinity for the two examined receptors [COX-2 (−19.4542 kcal/mol) and vascular endothelial growth factor receptor 2 (−17.6036 kcal/mol)]. The isolated compounds offered significantly active phytoconstituents for drug discovery and development.
Keywords: Rhododendron yunnanense, phenolics, quercitrin, molecular docking, VEGF-2, COX-2.